1975
DOI: 10.1002/chin.197545268
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: MANNICH‐REAKTION VON THIAZOLIDINONEN‐(4) UND CYCLISCHEN AMINEN

Abstract: Die Umsetzung von 2‐Imino‐3‐aryl‐4‐oxo‐thiazolidinen (I) mit Formaldehyd (II) und den cyclischen Aminen (III) führt zu den Mannich‐Basen (IV) bzw. (VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Svetkin et al 209 further reported the Mannich reaction of 2-imino-3-aryl-4-thiazolidinones with secondary amines and formaldehyde, giving products of type 199 and 200. l,2-Bis(2-phenyl-4-oxothiazolidin-3-yl)ethane obtained by the reaction of dibenzal ethylenediamine with thioglycolic acid in dry benzene is oxidized to dioxides 201 by heating in AcOH and 33% hydrogen peroxide. 117 However, 4-thiazolidinones on treatment with 30% H202 in a mixture of cold acetic acid and acetic anhydride give the 4-thiazolidinone S-monooxide deriva-tives210 (202).…”
Section: + R2nh Hcho Tx Chjnrjmentioning
confidence: 99%
“…Svetkin et al 209 further reported the Mannich reaction of 2-imino-3-aryl-4-thiazolidinones with secondary amines and formaldehyde, giving products of type 199 and 200. l,2-Bis(2-phenyl-4-oxothiazolidin-3-yl)ethane obtained by the reaction of dibenzal ethylenediamine with thioglycolic acid in dry benzene is oxidized to dioxides 201 by heating in AcOH and 33% hydrogen peroxide. 117 However, 4-thiazolidinones on treatment with 30% H202 in a mixture of cold acetic acid and acetic anhydride give the 4-thiazolidinone S-monooxide deriva-tives210 (202).…”
Section: + R2nh Hcho Tx Chjnrjmentioning
confidence: 99%
“…The imino nitrogen appears also to be a very efficient nucleophilic center [37]. Despite the fact that 2-iminothiazolidin-4-one (3) has four nucleophilic reaction centers, viz., the two nitrogens (imino and amido), oxygen and C 5 atoms, its aminomethylation usually takes place only at the ring nitrogen atom [38,39] or, if it is substituted, at the exocylic nitrogen atom [40,41].…”
Section: Structure and Basicitymentioning
confidence: 99%